2022
DOI: 10.1039/d1nj05561e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced water-resistant performance of Cu-BTC through polyvinylpyrrolidone protection and its capture ability evaluation of methylene blue

Abstract: Water instability issue greatly restrict the application of Cu-BTC for cationic dye (e.g. methylene blue (MB)) capture from wastewater. In the present contribution, polyvinylpyrrolidone (PVP) thin film was novelty grew...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…The XRD results of the Cu-BTC and Cu-BTC(OMe50) structures exhibited significant peaks like (220), ( 222), (400), (422), and (333), representing the sharp and symmetrical reflections observed at 2y = 6.71, 9.51, 11.61, 13.51, and 17.51, which indicate the formation of the Cu-BTC structure. [32][33][34][35] However, these characteristic peaks were not observed for the XRD results of the Cu-OMe sample, which is consistent with the SEM result. In contrast, the XRD study demonstrated that the Cu-BTC(OMe50) still had the appearance and crystal shape of Cu-BTC, even when the doping amount of 5-methoxyisophthalic acid reached 50 wt%.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The XRD results of the Cu-BTC and Cu-BTC(OMe50) structures exhibited significant peaks like (220), ( 222), (400), (422), and (333), representing the sharp and symmetrical reflections observed at 2y = 6.71, 9.51, 11.61, 13.51, and 17.51, which indicate the formation of the Cu-BTC structure. [32][33][34][35] However, these characteristic peaks were not observed for the XRD results of the Cu-OMe sample, which is consistent with the SEM result. In contrast, the XRD study demonstrated that the Cu-BTC(OMe50) still had the appearance and crystal shape of Cu-BTC, even when the doping amount of 5-methoxyisophthalic acid reached 50 wt%.…”
Section: Resultssupporting
confidence: 84%
“…Cu-BTC was synthesized using a similar procedure to that presented in the literature (Scheme S2, ESI †). 33,34 Typically, 0.5 g of Cu(NO 3 ) 2 Á3H 2 O and BTC were accurately weighed into the mixed solution of ethanol (8.5 mL), N,N-dimethylformamide (DMF) (8.5 mL), and water (8.5 mL). The mixture was evenly mixed by ultrasound for 30 min, and then transferred to a polytetrafluoron reactor at 85 1C for 20 h. After cooling to room temperature, the mixture was filtered and washed with DMF and ethanol in turn.…”
Section: Synthesis Of Cu-btcmentioning
confidence: 99%
“…Cu-BTC-NH 2 was synthesized with a slight modification according to the literature. , Typically, Cu­(NO 3 ) 2 ·3H 2 O (1 g), H 3 BTC (0.75 g), and 5-aminoisophthalic acid (0.25 g) were dissolved in 17 mL of equal volume of DMF, deionized water, and anhydrous ethanol mixed solution by ultrasound. Then, the solution was transferred into a Teflon-lined autoclave and reacted at 85 °C for 20 h. The product was filtered and washed with DMF and ethanol in turn and finally dried under vacuum at 80 °C to obtain the blue powder.…”
Section: Methodsmentioning
confidence: 99%
“…4 Each BTC (1,3,5-benzenetricarboxylate) ligand holds dimeric Cu paddles and forms a microporous open framework. 5,6 The presence of an unsaturated open Cu-metal center provides a partial positive charge in the structure, thus contributing to any electrostatic interactions of Cu-BTC with partially negatively charged molecules. 7 These open metal sites have also high affinities for small molecules containing lone pairs of electrons such as H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Among MOF materials, copper(II)–benzene‐1,3,5‐tricarboxylate (Cu‐BTC) is one of the most studied MOFs, having two octahedrally coordinated Cu atoms, which are connected to eight oxygen atoms of tetracarboxylate units 4 . Each BTC (1,3,5‐benzenetricarboxylate) ligand holds dimeric Cu paddles and forms a microporous open framework 5,6 . The presence of an unsaturated open Cu‐metal center provides a partial positive charge in the structure, thus contributing to any electrostatic interactions of Cu‐BTC with partially negatively charged molecules 7 .…”
Section: Introductionmentioning
confidence: 99%